Working time accounts and unemployment - Andrey Launov; Klaus Wälde (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Working time accounts allow rms to smooth their demand for hours employed. Descriptive literature suggests that this reduces turnover and inhibits increase in unemployment during recessions. We model theoretically the optimal choice of hours by a rm with a working time account. We show that working time accounts do not necessarily imply lower turnover. Turnover and unemployment may be inhibited or catalyzed by working time account depending on whether a rm meets economic downturn with surplus or de cit of hours and on how productive this rm is. Adjustment pattern in Germany implies that working time accounts have contributed positively.
Keywords: J23; J63; J64; 330